Consequences of exposure to sexual harassment among women working in hospitality workplaces in Bahir Dar City, Ethiopia: a structural equation model - Mulugeta Dile Worke; Zewdie Birhanu Koricha; Gurmesa Tura Debelew (BMC, 2023)
Abstract Introduction Sexual harassment is undoubtedly widespread, and many countries have enacted laws to punish and prevent it as insulting behavior. However, its impacts on the job, psyche, and physical health, especially reproductive health, are still severe and noticeable. Thus, this study aimed to examine the impacts of sexual harassment on the job, psychology, physical health, and reproductive health of women in the hospitality industry. Methods Institution-based cross-sectional survey was conducted between October 1 and November 30, 2021. Data were collected among 689 women who experienced sexual harassment in the hospitality industry. In selecting the participants, two-stage cluster sampling techniques were used. The data collection was carried out in two complementary ways. The model of structural equations examines the relationship between the experience of sexual harassment and coping with consequences. The associations were confirmed via AMOS 23. Results Sexual harassment positively predicted job outcomes and negatively predicted physical health. In contrast, coping with sexual harassment positively predicts health at work and in the body and is negatively associated with health in reproduction. Physical health fully mediated the link between sexual harassment (β = 0.017, t = 0.85, p = 0.022) and reproductive health outcomes and partially mediated (β = -0.021, t = -1.235, p = 0.017) between sexual harassment coping and physical health. The interaction between sexual harassment experiences and work experiences also strengthens the negative relationship between sexual harassment experiences and physical health. Conclusions The impact of sexual harassment on women's reproductive health was investigated in this study. It expands awareness of the effects of sexual harassment exposure, how to survive it, and how to establish effective preventative strategies, particularly in the hospitality industry. Effective prevention depends on preventing psychological and physical health, ultimately improving reproductive health. Thus, safe workplace initiatives and reproductive health care services are needed. Hospitality organizations should also devise a strategy for providing a supportive environment that can significantly improve women's health.